View-OD: a view model for ontology-based databases. (1st January 2013) - Bachtarzi, Chahinez; Benchikha, Fouzia
A new tendency for the conception of databases consists of storing in the same repository data and the ontology which indexes them by their semantics. These ontology-based databases (OBDB) systems offer a unique vision to exploit both ontological concepts and their extensions. However, users' applications need to have different and personalised views on the stored ontology and the integration of an appropriate view mechanism is required. In this paper, we propose to extend the traditional OBDB model to support multiple descriptions of the ontological data under customised view ontologies. These views consist of meaningful portions of the main ontology that can be restructured. We first present an approach using viewpoints to provide extensive descriptions of concepts which operate on the views to offer customised visions on them. Then we give the formalisation of the underlying model which allows multiple modelling of the ontological data. Specifications and implementation issues are also presented.